Iranian Women's Strategies for Coping with Domestic Violence - Taherkhani; Negarandeh; Simbar; Ahmadi (Kashan University of Medical Sciences, 2016)
Background Behavioral coping strategies may lead to either increased or reduced violence or associated stress, while also affecting psychological outcomes. To help abused Iranian women cope better with domestic violence and to provide better care for them, it is crucial to investigate their strategies for coping with domestic violence. Objectives This qualitative study explores the strategies used by Iranian women to cope with domestic violence. Materials and Methods This study uses a qualitative design, based on a content analysis approach. The participants comprised 24 married women, selected from parks, health centers and two colleges located in Tehran, Iran. The purposive sampling method was used to recruit the participants and continued until data saturation was reached. Semi-structured interviews were carried out to gather data. Results During the data analysis, a theme "situation management" emerged together with two categories, comprising "the strategies of violence control" and "the strategies of distress control". The results show that the participants try to manage the abusive situation by controlling violence and or the distress it causes. Conclusions Unlike common stereotypes that reveal women to be submissive and passive in the face of violence, the results show that the participants in this study coped with violence using consciousness and creativity, and by relying on the available resources. An understanding of the coping strategies used by abused women could help health staff to provide better care for such women and encourage them to use more effective strategies.